Pseudoboletus silvaticus (Boletaceae, Basidiomycota), a new species from Mexico - Cortés-Pérez, Alonso; Ramírez-Guillén, Florencia; García-Jiménez, Jesús; Ramírez-Cruz, Virginia; Villalobos-Arámbula, Alma Rosa; Barragán Reynaga, Dolores Marina; Guzmán-Dávalos, Laura (Phytotaxa, 2023)
The genus Pseudoboletus includes parasitic fungi and is well known in temperate zones. In this paper, we present the first Mexican collections of this genus. Two specimens were collected in a field expedition in a tropical montane cloud forest on the San Martín Tuxtla volcano, Veracruz, Mexico, resulting in a new species of Pseudoboletus, which grows on fruiting bodies of Scleroderma nitidum. Descriptions, illustrations, and photographs of P. silvaticus sp. nov. are provided. Also, its phylogenetic position in the Boletineae tree was inferred using nuclear 28S rDNA (28S) and translation elongation factor-1α (tef–1α) with Maximum Likelihood method and Bayesian Inference. Comparison between nuclear rDNA internal transcribed spacer region (ITS) sequences of P. parasiticus from North America and Europe and the new taxon were made. The original diagnosis of the genus Pseudoboletus is emended to include this new species.